Pulmonary synovial sarcoma. (2018) - Gupta, Ankit; Palkar, Atul; Narwal, Priya; Kataria, Ashish
Abstract: Primary Synovial sarcoma of the lung is an extremely rare entity. Our patient was healthy prior to presentation and came in with a short course of dyspnea and was found to have a large synovial sarcoma on the lung.